Rethinking Language - From `Challenging Behaviour to `Behaviours That Challenge - Doyle, Carmel; Fleming, Sandra; Cleary, Michelle; Mc Mahon, Martin; Eustace-Cook, Jessica (My University, 2025)
Aim: The aim of this presentation is to explore the use of the term ‘challenging behaviour’ and alternative terms. This work formed part of a scoping review exploring the factors that may lead to development of behaviours that challenge and prevention and management of crisis situations among CYA with disability, more specifically intellectual disability and autism. Background: The term challenging behaviour has been in use for at least three decades (Royal College of Psychiatrists, 2016). In recent years there appears to be inconsistency in use of language with a variety of terms in existence. Methods: A scoping review methodology guided by Arksey and O’Malley’s framework was adopted. Searches were undertaken in online databases for publications over a 10-year period. Additionally, grey literature was searched. Strict inclusion criteria were also applied. Findings: The most commonly used phrase was challenging behaviour/s. A total 149 (of 247) papers adopted terms to describe behaviour that challenges. Alternative terms were identified from the literature and are presented in more detail here. Conclusions: While challenging behaviour is the most frequently cited term within the literature, there is inconsistency in use of language. It is evident that language used can shape individuals’ thoughts, beliefs and emotions and can influence wider society (Chan et al., 2012). Therefore, taking cognisance of the NICE guidelines (NICE 2015) and the NDA guidance on disability language and terminology (NDA 2022) and what is deemed acceptable person-centred terminology by individuals, the term ‘behaviours that challenge’ is preferred as an alternative.
IASSIDD 5th Asia-Pacific Congress
PRESENTED
https://static1.squarespace.com/static/6780e7e3d817071740107647/t/68ee27a3e5dee35636b6bef0/1760438179380/Compiled+Abstracts+and+Proposals+%2814Oct2025%29.pdf https://static1.squarespace.com/static/6780e7e3d817071740107647/t/68ef219b18ba2f256109de62/1760502171864/IAPC+2025+-+Main+Congress+%2815+to+17+Oct%29+Programme+Outline.pdf
Singapore
Keywords: Inclusive Society; Intellectual Disability; Intellectual Disability; Children